Witches, tea plantations, and lives of migrant laborers in India - Soma Chaudhuri (Foundation Books, 2013)
Bringing together a holistic theoretical perspective drawing from sociology, anthropology, and postcolonial history, the author argues that witchcraft accisations among the adivasi worler communities in the tea plantations of West Bengal are a protest against the plantation management.